Repetitive elements in parasitic protozoa - Clayton, Christine (BMC biology, 2010)
A recent paper published in BMC Genomics suggests that retrotransposition may be active in the human gut parasite Entamoeba histolytica. This adds to our knowledge of the various types of repetitive elements in parasitic protists and the potential influence of such elements on pathogenicity.